2021
DOI: 10.1101/2021.07.16.452635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining ancestral reconstruction with folding-landscape simulations to engineer heterologous protein expression

Abstract: Obligate symbionts exhibit high evolutionary rates and extensive sequence divergence. Here, we use the thioredoxin from Candidatus Photodesmus katoptron, an uncultured symbiont of flashlight fish, to explore evolutionary and engineering aspects of protein folding in heterologous hosts. The symbiont protein is a standard thioredoxin in terms of 3D-structure, stability and redox activity. However, its refolding in vitro is very slow and its expression in E. coli leads to insoluble protein. By contrast, resurrect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Ancestral sequence reconstruction has been amply used in the post-genomic era as a tool to address fundamental problems in molecular evolution [3][4][5]. Furthermore, it has been found that ancestral proteins "resurrected" in the lab (i.e., the proteins encoded by the reconstructed sequences) often display interesting and even extreme properties [6][7][8][9][10][11][12][13][14][15][16] plausibly reflecting ancestral adaptations to unusual intra-and extra-cellular environments. Resurrected ancestral proteins often display high stability, supporting the frequently hypothesized thermophilic nature of ancient life.…”
Section: Introductionmentioning
confidence: 99%
“…Ancestral sequence reconstruction has been amply used in the post-genomic era as a tool to address fundamental problems in molecular evolution [3][4][5]. Furthermore, it has been found that ancestral proteins "resurrected" in the lab (i.e., the proteins encoded by the reconstructed sequences) often display interesting and even extreme properties [6][7][8][9][10][11][12][13][14][15][16] plausibly reflecting ancestral adaptations to unusual intra-and extra-cellular environments. Resurrected ancestral proteins often display high stability, supporting the frequently hypothesized thermophilic nature of ancient life.…”
Section: Introductionmentioning
confidence: 99%